(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
Fused Deposition Modelling process is an additive manufacturing process influenced by numerous parameters that has an impact on strength of the components. This paper is dedicated to study the impact of Fused Deposition Modelling parameters on the strength of PLA/Copper infill composites. Influence on tensile, impact and flexural strengths were studied by varying the process parameters. Nozzle Temperature, Layer Thickness, Printing speed and Infill density are the major fused deposition modelling parameters considered in this study. Mathematical models were developed to predict the strength of composites by varying the process parameters. Strength of the composites diminished with rise in layer thickness and printing speed. On the other hand, increase in nozzle temperature and infill density increased the strength of the composites. The composite samples were subjected to characterization analysis to have an idea on the fracture mechanisms. Both brittle and tensile mode of failure is observed in the samples influenced by the process parameters that affect bonding of layers and porosity.